Commitment of Senior Management towards Public Sector Transformational Change: A Rasch Analysis - Nazirah AZIZ; Emmarelda Maswesi AHMAD; Zamalia MAHMUD; Jamaliah SAID (Communications of International Proceedings, 2020)
In enhancing the performance of civil services, the Government of Malaysia has taken extensive change initiatives to continuously reform the administration of the public sector in Malaysia. The transformation programme has been introduced to improve the overall performance of civil personnel and to improve the delivery of services towards the public at large. Among other change initiatives taken is strengthening the Performance Measurement System (PMS) towards improving the performance of civil personnel and public sector organizations.  The purpose of this study is to provide an extensive review of past literatures regarding financial management reforms in the Malaysian public sector organization which brings to the establishment of PMS. This study also aims to explore the pattern of senior management commitment in predicting their readiness towards public sector transformational change. A total of 40 useable responses were collected from May to August 2015 using a web-based survey. Data were analyzed using Rasch measurement and Winsteps@ 3.72.3. The study showed that the public sector managers seriously recognize the role and commitment of senior management as an important driver towards the successful implementation of change in Malaysia. This study also found that longer-tenured managers with several numbers of working experience are more committed to change than less tenured managers with limited experience. Findings from this study are expected to benefit the authorities by assisting them in executing their roles to ensure the public sector managers accept change and able to improve their performance as to support the government aspiration.
Keywords: Performance Measurement; Public Sector Organization; Rasch Measurement Model.